KELIMPAHAN DAN DISTRIBUSI LARVA IKAN DI PERAIRAN PESISIR LAMPUNG TIMUR - Sagala, La Ode Syahlan S; Kamal, Mohammad Mukhlis; Zairion, Mr.. (JFMR (Journal of Fisheries and Marine Research), 2020)
Information abundance and distribution of fish larvae in coastal waters of East Lampung currently very limited. The research aimed to improve the knowledge of the early life of organisms, in order to manag biodiversity and biological resources in the waters. Research station representing the several water sectors: in-shore, near-shore, and off-shore. The research was a representation of eastern monsoon (June) and transition monsoon (September) in 2017. Fish larvae was harvested using bonggo-net tool while its identification to family level using portable Dino-lite. Based on the result the Abundance of fish larvae in eastern monsoon was higher than transition monsoon. This research found 81 families of fish larvae. There were 10 dominant families, that are Gobiidae, Pegasidae, Mullidae, Pomacentridae, Sillaginiidae, Bleniidae, Bythitidae, Carangidae, Pseudochromidae and Bothidae. The distribution of fish larvae in the lower in-shore was higher than near-shore and off-shore, while east and transitional seasons have not much different larval catches.Â  Temperature, salinity and pH parameters indicated optimal range state for survival and growth of fish larvae, brightness and turbidity in accordance with water quality standards, currents velocity on eastern monsoon is very fast while transition monsoon is fast to very fast. Phytoplankton and zooplankton showed sufficient natural food availability for the life of fish larvae. Result Canonnical Corespondence Analysis (CCA) analysis to connectivity of abundance and larvae distribution showed that the brightness parameter forming a point projection while other water environment condition parameters form a vector projection in both period of monsoon. The abundance and fish larvae distribution in coastal waters of East Lampung in all three sectors of the waters had proportionality to the parameters of environmental conditions, especially the current parameters and the difference of the monsoon period.